A rare case report: heterotopic pregnancy with ovarian ectopic pregnancy - N., Manuja; Devoor, Ashok; ., Umashankar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Heterotopic Pregnancy(HP) is defined as the occurrence of intrauterine and extrauterine pregnancy simultaneously. Incidence varies from 1 in 8000 to 30,000 natural conceptions. HP is common with artificial reproductive techniques and is very rare in natural conception. A high index of suspicion is helpful in diagnosis and appropriate management. We report a case of HP in a 28-year-old woman presented with 2 and half months amenorrhoea, pain abdomen and bleeding per vagina with TAS showing intra uterine single missed abortion and ovarian ectopic pregnancy.